Commitment to pay taxes: Results from field and laboratory experiments - Ann-Kathrin Koessler; Benno Torgler; Lars P. Feld; Bruno S. Frey (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2018)
The ability of a tax authority to collect taxes successfully depends on both its relationship with taxpayers and how strongly these taxpayers are committed to contributing to the common good. We present field and laboratory experimental evidence on a new non-intrusive approach aimed at fostering the commitment to pay taxes. Using a between-subject design in a unique field setting, we analyze whether tax compliance changes if taxpayers receive an offer to promise paying their taxes on time. Taxpayers who complied with the promise entered into a lottery with the chance of winning either a financial or a non-financial reward. Rewards were also offered in response to compliance only (i.e., without being asked to make a formal promise) allowing us to disentangle a pure reward effect from the commitment effect. As potential legal obstacles prevented us from developing a treatment that allowed for identifying whether the promise itself changes behavior, we designed and conducted a laboratory experiment to test this proposition. In the field experiment, taxpayers with a history of being compliant are more likely to make a promise. Similarly, the laboratory experiment indicates that individuals with higher tax morale are more compliant and more likely to make the promise. In addition, for all promise schemes, compliance is significantly higher for the promise-makers as compared to subjects in the control group and to those who did not make a promise. The field experiment indicates that commitment can improve payment behavior. This effect, however, is strongly dependent on the type of reward to which the promise is linked. Compliance increases only if the reward is non-financial. A no compliance effect is observed if cash is offered in return for promise fulfilment. A strong compliance effect for pure non-financial rewards was also obtained in the laboratory experiment.
Keywords: H26; C93; C91; A13; 330; tax compliance; field experiment; commitment; promise; supportive incentives; psychological contract